Comparative Analysis of Corn Farming Income Between Good Agricultural Practice and Conventional Systems in Tilongkabila District, Bone Bolango Regency - Ramlan Mustafa; Adeliyan A. Husain; Zulham Sirajuddin (Majapahit Journal of Islamic Finance and Management, 2025)
This study aims to: increase corn farming income using the Good Agricultural Practices system with conventional in Tilongkabila District, Bone Bolango Regency, and analyze the income comparison between the Good Agricultural Practices system and conventional in corn farming in Tilongkabila District, Bone Bolango Regency. This research was conducted in October-January 2025. The research method used a survey method, and the questionnaire, as a research tool, was an income analysis and a Mann-Whitney independent test analysis. The results of this study indicate that the total income of corn farmers using the Good Agricultural Practices system is Rp. 168,615,622 with an average income cost of Rp. 6,245,023/farmer or Rp. 4,783,422/Ha, and the total income for corn farmers using the conventional system is Rp. 82,676,066 with an average income cost of Rp. 3,592,612/farmer or Rp. 2,850,899/Ha; and the results of the Mann-Whitney Independent Sample Test analysis, there is a significant difference between the income of farmers who use the Good Agricultural Practices system and the conventional system in Tilongkabila District, Bone Bolango Regency.